Comparison of Pregnancy Outcome in Placenta Previa versus Placenta Abruption - Naamat Abid,; Laila Benhamida,; Maha Alzergany,; Mona Bin Salah,; Salma Almeslati, (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Placenta previa and placenta abruption (abruptio placenta), the two leading and major causes of antepartum hemorrhage, result in substantial maternal and perinatal morbidity and mortality. This study was conducted to compare the fetal and maternal outcome of patients with abruption placenta and placental Previa. Methods. This was comparative retrospective case series study was conducted in the Department of Obstetrics and Gynecology, at university Tripoli hospital during the year 2017. After taken ethical approval, and by convenience sampling method, including seventy patients (35 with placenta previa and 35 with placental abruption) who diagnosed by ultrasound. The following data was obtained from the files: the age, gravidity, parity, history of previous abortion, history of bleeding, maternal outcome, mode of delivery, and fetal outcome. Statistical Package for the Social Science version 24 was used for analysis. Results. The study showed no significant differences between the two groups in term of gravidity, parity, previous abortion, and the bleeding in previous pregnancies. About 5.7% of Previa groups had Antepartum haemorrhage (APH). Postpartum hemorrhage (PPH) were 11.4% of the Previa group. Only 1 case of the previa group had intrapartum bleeding. 42.8% pregnant women had hypertension in abruption group. Only abruption group had diabetes with percentage of (22.9%), Preterm premature rupture of the membranes (PPROM) was higher in the abruption group (25.7%), while anemia was higher in the Previa group (48.6%). Conclusion. Abruption placenta was associated with younger age, hypertension, diabetes, PROM, prematurity, fetal death, and neonatal resuscitation. Placenta previa was associated with older age, anemia, and nursery admission. Early detection, provision of antenatal care, and emergency obstetric care services can reduce the negative effects of APH.